Mitigation of New Normal Life as A Sustainable Effort to Prevent the Transmission of Covid-19 - Marylin S. Junias; Norman Delvano Weky; Dionesia Kidi Making; Claudya S. Virlynriana S; Arja Fitri; Junia Jessy Sarupy; Reny Martini Kosat (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Coronavirus caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a virus that can infect the respiratory tract. The disease caused by this viral infection is called COVID-19. The Coronavirus can cause mild respiratory disorders, severe lung infections, and even death. The Case of COVID-19 epidemic first broke out in Wuhan, China in December 2019 and has been spread quicklyto various parts around the world. This pandemic has affected various societal and economic changes not only in Chine but also in all affected countries around the world. Efforts to prevent transmission known as 5M (wearing protective face mask,maintaining distance, washing hands with soap, staying away from crowds, and reducing mobilization) arecontinuously being improved. This service activity is carried out with the aim of increasing public knowledge and understanding about COVID-19, vaccination, and encouraging people to want to do vaccinate against COVID-19. Using the Participatory Action Research (PAR) method. This activity included distributing protective face masks, placing COVID-19 transmission prevention banners, demonstratingthe proper hand washing steps, GERMAS (Healthy Living Community Movement) for non-smoking areas by affixing stickers. This activity was carried out at the Stasi Sta. Maria Imaculata Oeltua, Taebenu District, Kupang Regency, East Nusa Tenggara on November 20, 2022, at 10 a.m until 12.30 p.m. The target of this extension was the people in Oeltua Village, Taebenu District, Kupang Regency, East Nusa Tenggara. The total number of people present was 50 people. The result of this extension is an increased understanding of the Oeltua Village community in implementing the 5M to prevent Covid-19 transmission in the era of new normal life